To the charging of sphere in a EHD gas flow - Sorokin, A.E. (Вопросы атомной науки и техники, 2007)
The interaction between conducting sphere and ions has been investigated in a presence of external electric field and electrohydrodynamic (EHD) gas flow. Gas is considered as weakly ionized under atmospheric pressure. Diffusion is assumed to be weak and the trajectory assumption is taken into consideration. Ion currents are obtained analytically and investigated numerically for the collinear electric field and gas flow vectors. It is shown, that sphere charging regimes depend on the key parameter ξ± - the relation of ion drift velocity far away from sphere to gas velocity. So, the cases |ξ±| < 1 and |ξ±| > 1 yield to different charging regimes. For the potential flow, the ion current has been found analytically in continuous ξ± -parameter space. Досліджено взаємодію провідної сфери і електрогідродинамічного (ЕГД) газового потоку в присутності зовнішнього електричного поля. Газ передбачається слабко іонізованим. Дифузія іонів нехтується, враховується тільки їхній дрейф і перенос потоком газу. Аналітично і чисельно отримані іонні струми на сферу для випадку потенційного обтікання для будь-яких значень керуючого параметра ξ± - відношення швидкості дрейфу іонів в однорідному електричному полі до швидкості газу удалині від поверхні сфери. Исследовано взаимодействие проводящей сферы и электрогидродинамического (ЭГД) газового потока в присутствии внешнего электрического поля. Газ предполагается слабо ионизованным. Диффузией ионов пренебрегается, учитывается только их дрейф и перенос потоком газа. Аналитически и численно получены ионные токи на сферу для случая потенциального обтекания для любых значений управляющего параметра ξ± - отношение скорости дрейфа ионов в однородном электрическом поле к скорости газа вдали от поверхности сферы.